Preparation and properties characterization of gallic acid epoxy resin/succinic anhydride bionanocomposites modified by green reduced graphene oxide. Issue 1 (2nd January 2016) - Hou, Guixiang; Gao, Jungang; Xie, Jianqiang; Li, Bo
ABSTRACT: Graphene oxide was reduced into reducing-graphene oxide (r-GO) successfully using gallic acid (GA) as a green reducing agent. Biobased gallic acid epoxy resin (GAER) was synthesized from renewable GA, and the biobased GAER/r-GO nanocomposites and glass fiber-reinforced composites were prepared with succinic anhydride as a curing agent. The dynamic mechanical, thermal, and mechanical properties of the composites with varying r-GO contents were characterized. When the content of r-GO was 0.5 wt%, the glass transition temperature was 10.4°C higher than the pure resin system. The thermal and mechanical properties were increased with increasing r-GO content; when the r-GO content was 1.0 wt%, the initial degradation temperature was enhanced by approximately 6.8°C, the tensile and impact strengths were 34.5% and 49.1% higher, respectively, than the pure cured GAER. The impact strength of GAER was higher than that of the bisphenol A epoxy resin/SUA curing system, but the tensile strength was lower than it.